Upregulation of Cartilage Oligomeric Matrix Protein and Bone Morphogenetic Protein-2 May Associate with Calcific Aortic Valve Disease. Issue 2 (6th June 2021) - Xu, Yueyue; Cao, Yide; Liu, Yafeng; Wang, Jingsong; Chen, Ganyi; Tao, Zhonghao; Yao, Yiwei; Cai, Yuchen; Wu, Yunzhang; Chen, Wen
Abstract: Objective: Calcific aortic valve disease (CAVD) affects millions of elderly people, and there is currently no effective way to stop or slow down its progression. Therefore, exploring the pathogenesis of CAVD is very important for prevention and treatment. Cartilage oligomeric matrix protein (COMP) have important role in cell phenotype change. This study is aimed to confirm whether COMP participate in CAVD and try to find the possible mechanisms. Methods: Human aortic valve tissues from Nanjing First Hospital (CAVD group, n  = 20; control group, n  = 11) were harvested. The expression level of COMP was tested by western blot and immunohistochemistry. Dual immunofluorescence staining was used for locating COMP. Bone morphogenetic protein-2 (BMP2) signalling were tested by western blot. The animal model was also used to detect COMP level by immunohistochemistry. Results: The results showed that the expression level of COMP was significantly increased in the calcific valve samples when compared with that of the control valve ( P  < 0.05); COMP was expressed near the calcific nodules and co-localized with α-smooth muscle actin (α-SMA). The protein levels of BMP2 and p-Smads 1/5/9 were markedly more highly expressed in the CAVD group than the control group ( P  < 0.05). Furthermore, immunofluorescence detection showed that COMP and BMP2 were co-located in calcific valves. Conclusions: The above results suggested that upregulation of COMP and BMP2 may be associated with aortic valve calcification and that COMP may become a potential therapeutic target in human CAVD.